Who controls the preparation of education administrators? - Danzig, Arnold Bob, 1948-; Black, William R. (Research and theory in educational administration., 2019)
"This is the first book in the re-imagined series Research and Theory in Educational Administration. The volume includes a variety of perspectives written by university professors in the field of educational administration, which moves our thinking beyond the traditional scope of organizational theory and institutional analysis. It is this combination of theory, of new directions in leadership preparation and new narratives of participation that we hope will contribute to a more engaging volume for its readers -- graduate students, researchers, and practitioners. The volume will provide evidence of and explanation for changing patterns of institution production explored through academic and epistemic drift. It also provides a deeper understanding of how state regulation is related to the school administrator pipeline or pathways. The concepts explained and illustrated in the volume hopes to provide a better framework for understanding how administrator preparation is unfolding across the U.S. and internationally, as well as the direction of the field of educational administration in the future"--